PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL MELALUI KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL PEMODERASI - Sentosa, Aylicia; Purwanto, Marini; Mulia, Teodora Winda (Jurnal Akuntansi Kontemporer, 2013)
The budget is important in the company. Companies need to develop a budget to determine the company's strategic plan is usually done by the top management. Usually can cause stiffness in the control of the budget. To anticipate the company's participa-tory budget needed to motivate subordinates performance. Therefore, it is necessary to support participatory budgeting organiza-tional commitment and leadership style. This study discusses the effect of budgetary participation on managerial performance through organizational commitment and leadership style as a variable pemoderasi. Object of this study is the branch leaders, manag-ers, accountants, bank marketing section in Surabaya. Data collection methods used in this study is a questionnaire method. Data were obtained from questionnaires by the number of data entry by 65 respondents. The results of this study indicate that the first hypothesis test results showed significant positive budgetary participation on managerial performance. Second, the moderating effect of organizational commitment in the budgetary participation will not have a positive and significant impact on managerial perfor-mance. Third, the moderating influence of leadership style budgetary participation will have a positive and significant impact on managerial performance.